Toward Establishing Core Outcome Domains For Trials in Kidney Transplantation: Report of the Standardized Outcomes in Nephrology—Kidney Transplantation Consensus Workshops. Issue 8 (August 2017) - Tong, Allison; Gill, John; Budde, Klemens; Marson, Lorna; Reese, Peter P.; Rosenbloom, David; Rostaing, Lionel; Wong, Germaine; Josephson, Michelle A.; Pruett, Timothy L.; Warrens, Anthony N.; Craig, Jonathan C.; et al.
Abstract : Background: Treatment decisions in kidney transplantation requires patients and clinicians to weigh the benefits and harms of a broad range of medical and surgical interventions, but the heterogeneity and lack of patient-relevant outcomes across trials in transplantation makes these trade-offs uncertain, thus, the need for a core outcome set that reflects stakeholder priorities. Methods: We convened 2 international Standardized Outcomes in Nephrology-Kidney Transplantation stakeholder consensus workshops in Boston (17 patients/caregivers; 52 health professionals) and Hong Kong (10 patients/caregivers; 45 health professionals). In facilitated breakout groups, participants discussed the development and implementation of core outcome domains for trials in kidney transplantation. Results: Seven themes were identified. Reinforcing the paramount importance of graft outcomes encompassed the prevailing dread of dialysis, distilling the meaning of graft function, and acknowledging the terrifying and ambiguous terminology of rejection. Reflecting critical trade-offs between graft health and medical comorbidities was fundamental. Contextualizing mortality explained discrepancies in the prioritization of death among stakeholders—inevitability of death (patients), preventing premature death (clinicians), and ensuring safety (regulators). Imperative to capture patient-reported outcomes was driven by making explicit patient priorities, fulfilling regulatory requirements, and addressing life participation. Specificity to transplant ; feasibility and pragmatism (long-term impacts and responsiveness to interventions); and recognizing gradients of severity within outcome domains were raised as considerations. Conclusions: Stakeholders support the inclusion of graft health, mortality, cardiovascular disease, infection, cancer, and patient-reported outcomes (ie, life participation) in a core outcomes set. Addressing ambiguous terminology and feasibility is needed in establishing these core outcome domains for trials in kidney transplantation. Abstract : Standardized Outcomes in Nephrology-Kidney Transplantation (SONG-Tx) convened 2 international consensus workshops in Boston and Hong Kong with patients/caregivers and health professionals to discuss the development and implementation of core outcome domains for trials in kidney transplantation. Supplemental digital content is available in the text.